2023
DOI: 10.1177/13524585231166834
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MRI T2-lesion evolution in pediatric MOGAD, NMOSD, and MS

Abstract: Background: Magnetic resonance imaging (MRI) T2-lesions resolve more often in myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) than aquaporin-4 IgG-positive neuromyelitis optica spectrum disorder (AQP4 + NMOSD) and multiple sclerosis (MS) in adults but few studies analyzed children. Objective: The main objective of this study is to investigate MRI T2-lesion evolution in pediatric MOGAD, AQP4 + NMOSD, and MS. Methods: Inclusion criteria were as follows: (1) first clinical attack; (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We did not find differences in acute MOGAD lesion dynamics between children and adults, and prior analyses of longer-term lesion evolution have shown similar rates of lesion resolution in pediatric and adult MOGAD, suggesting this is related to MOGAD disease biology rather than being age dependent. 10 - 12 A prior study showed new asymptomatic lesions in MOGAD were most commonly detected at the first follow-up MRI scan after an attack but rarely developed later in the disease course, differing from MS. 26 , 27 Our data suggest that these asymptomatic lesions may not develop between clinical attacks, but rather more likely arise within the prior attack but are not captured on the initial attack MRI due to radiologic lag.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find differences in acute MOGAD lesion dynamics between children and adults, and prior analyses of longer-term lesion evolution have shown similar rates of lesion resolution in pediatric and adult MOGAD, suggesting this is related to MOGAD disease biology rather than being age dependent. 10 - 12 A prior study showed new asymptomatic lesions in MOGAD were most commonly detected at the first follow-up MRI scan after an attack but rarely developed later in the disease course, differing from MS. 26 , 27 Our data suggest that these asymptomatic lesions may not develop between clinical attacks, but rather more likely arise within the prior attack but are not captured on the initial attack MRI due to radiologic lag.…”
Section: Discussionmentioning
confidence: 99%
“…14 Only 5 patients (4 of whom were adults) fulfilled the MOGAD criteria (i.e., they were MOG-Ab positive and had at least 1 supporting feature) but had a diagnosis of MS (e.g., false positive). In cases with diagnostic uncertainty, other factors, such as repeat testing in both the serum and CSF, 15 testing with live CBA, oligoclonal bands (which are more common in MS, although they can be seen in 20% of patients with MOGAD 16,17 ), and lesion dynamics on MRI 18,19 could be assessed over time to discriminate the demyelinating etiology, before commencing disease-modifying therapies.…”
Section: Discussionmentioning
confidence: 99%